2018
DOI: 10.1038/s41396-018-0241-7
|View full text |Cite
|
Sign up to set email alerts
|

Stressor interaction networks suggest antibiotic resistance co-opted from stress responses to temperature

Abstract: Environmental factors like temperature, pressure, and pH partly shaped the evolution of life. As life progressed, new stressors (e.g., poisons and antibiotics) arose as part of an arms race among organisms. Here we ask if cells co-opted existing mechanisms to respond to new stressors, or whether new responses evolved de novo. We use a network-clustering approach based purely on phenotypic growth measurements and interactions among the effects of stressors on population growth. We apply this method to two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 51 publications
3
68
0
Order By: Relevance
“…By using the Kirby-Bauer disk diffusion susceptibility test, Laganà et al ( 2019 ) confirmed that various bacterial isolates from macroplastics indeed showed multiple antibiotic resistances against cephalosporins, quinolones and beta-lactams. The high potential of bacterial antibiotic resistance on plastics could also be related to increased resistance to cold or heat stress (Cruz-Loya et al 2019 ) and light irradiation (Chen et al 2019b ), meaning that bacteria on plastics biofilms appear highly adaptable to a variety of environmental stresses. A recent study showed that microplastic biofilms also have the potential to increase the frequency of horizontal gene transfer, e.g.…”
Section: Microbial Communities Of Microplastic Biofilmsmentioning
confidence: 99%
“…By using the Kirby-Bauer disk diffusion susceptibility test, Laganà et al ( 2019 ) confirmed that various bacterial isolates from macroplastics indeed showed multiple antibiotic resistances against cephalosporins, quinolones and beta-lactams. The high potential of bacterial antibiotic resistance on plastics could also be related to increased resistance to cold or heat stress (Cruz-Loya et al 2019 ) and light irradiation (Chen et al 2019b ), meaning that bacteria on plastics biofilms appear highly adaptable to a variety of environmental stresses. A recent study showed that microplastic biofilms also have the potential to increase the frequency of horizontal gene transfer, e.g.…”
Section: Microbial Communities Of Microplastic Biofilmsmentioning
confidence: 99%
“…Understanding how the components of a complex biological system combine to produce the system’s properties and functions is a fundamental question in biology. Answering this question is central to solving many fundamental and applied problems, such as how multiple genes combine to give rise to complex traits ( Phillips, 2008 ; Mackay, 2014 ), how multiple drugs affect the evolution of resistance in bacteria and cancer cells ( Michel et al, 2008 ; Wood et al, 2014 ), how multiple environmental stressors affect bacterial physiology ( Cruz-Loya et al, 2019 ), or how multiple species affect the function of a microbial consortium ( Sanchez-Gorostiaga et al, 2019 ; Gould et al, 2018 ; Guo and Boedicker, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how the components of a complex biological system combine together to produce the system's properties and functions is a fundamental question in biology. Answering this question is central to solving many fundamental and applied problems, such as how multiple genes combine to give rise to complex traits [1,2] , how multiple drugs affect the evolution of resistance in bacteria and cancer cells [3,4] , how multiple environmental stressors affect bacterial physiology [5] , or how multiple species affect the function of a microbial consortium [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%